Sosialisasi dan Pendampingan Keputusan Badan Bahasa Kemendikbudristek Tentang Ejaan Bahasa Indonesia Yang Disempurnakan Untuk Pelajar Sekolah Dasar di Kabupaten Karanganyar - Esteen Arum Satyani; Aisyah Kharisma Yogi; Aulia Putri Damayanti; Imam Nurcahyono; Kundharu Saddhono (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Indonesian has a very important role in improving the quality of basic education. In its application, EYD is also adjusted to keep up with the times and technological advances. The socialization of EYD in elementary schools is the initial stage in ensuring that our young generation has a strong foundation in the use of correct and standard language. The research methods used include problem identification, preparation of training materials, training implementation, mentoring and monitoring, and evaluation and stabilization. The results obtained in this socialization include, among others, there are still many errors regarding the writing of geographical names, names of people, capitalization of prepositions, correct capital letters, writing letters, and the use of spaces use of spaces. Also, at the end of the activity, evaluation and stabilization activities were held for all students.